Experimental Measurements and Numerical Simulation of Bridge Construction Welding at Low Temperatures - Konar, Radoslav; Patek, Marek; Mician, Milos (Communications - Scientific letters of the University of Zilina, 2014)
This article describes experimental measurements and welding simulation by welding of bridge construction with thickness 30 mm. The welded bridge plate was made from steel S355. Welding was carried out at low ambient temperature. Welding parameters and temperature cycles were measured during welding. Deformations of welded construction were obtained using optical system TRITOP before and after welding process. Experimental results except for deformations were used as boundary conditions for FEM simulation in SYSWELD. Temperature cycles, angular deformations and residual stresses were computed. The values of computed and measured angular deformations are almost identical. It follows that SYSWELD is able to predict angular and linear deformation with a good accuracy.